2020
DOI: 10.1002/ps.5715
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐based evaluation of maize (Zea mays) and weed response to post‐emergence herbicide applications of Isoxaflutole and Cyprosulfamide applied as crop seed treatment or herbicide mixing partner

Abstract: BACKGROUND Some maize post‐emergence herbicides obtain their crop/weed selectivity only through the use of chemical crop safeners. Safeners improve the tolerance of maize to herbicidal active ingredients. In order to investigate the crop response to safener (cyprosulfamide) spray application and seed treatment, greenhouse and field trials were conducted on three maize development stages (2‐, 4‐, and 6‐leaf stage). Visual estimations on crop vitality were compared to ground‐based and airborne hyperspectral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The study showed that multi-spectral imagery was used for anomaly detection and a spectral linear unmixing-based approach with site-specific agriculture was used to quantify stress severity and detect prior infection. It was mentioned by Mink et al [64] that airborne multi-spectral imaging evaluation delivers more detailed and comprehensive information than data acquired in field trials visually.…”
Section: Multispectral Remote Sensing Imagery For Agricultural Purposementioning
confidence: 99%
“…The study showed that multi-spectral imagery was used for anomaly detection and a spectral linear unmixing-based approach with site-specific agriculture was used to quantify stress severity and detect prior infection. It was mentioned by Mink et al [64] that airborne multi-spectral imaging evaluation delivers more detailed and comprehensive information than data acquired in field trials visually.…”
Section: Multispectral Remote Sensing Imagery For Agricultural Purposementioning
confidence: 99%
“…25 Using herbicides composed of IXF and CSA is a successful path for weed control in conventional and herbicide-tolerant corn production system. 26,27 It was shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the benzenesulphonamide group as a chemical feature required for its safener activity. 28 Scaffold hopping and active substructure combination play an important role in drug discovery techniques which are beneficial to the discovery of potential agrochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Cyprosulfamide (CSA), a kind of herbicide safener invented by Bayer Crop Science in 2005, pertains to the chemical class of aromatic sulfonamides and was found to have an effect on preventing crop from herbicide injury 25 . Using herbicides composed of IXF and CSA is a successful path for weed control in conventional and herbicide‐tolerant corn production system 26,27 . It was shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the benzenesulphonamide group as a chemical feature required for its safener activity 28 …”
Section: Introductionmentioning
confidence: 99%
“…This is an important indicator for identifying plant species (Shapira et al, 2013). Many studies have reported that hyperspectral imaging is a powerful technology for detecting weeds because different species of plants showed different profiles of spectral reflectance (Farooq et al, 2019;Huang et al, 2016;Matzrafi et al, 2017;Mink et al, 2020;Okamoto et al, 2007;Pantazi et al, 2016;Suzuki et al, 2008;Zhang et al, 2019). Okamoto et al (2007) developed a portable hyperspectral imaging system that captured spectral images in the range of 400 to 1000 nm with 10 nm resolution and successfully identified buckwheat (Fallopia convolvulus), field horsetail (Equisetum arvense), green foxtail (Setaria viridis (L.) P.…”
mentioning
confidence: 99%